Cutis marmorata as a manifestation of decompression illness (Emergency Care Journal, 2020)
We present imagines of skin lesions due to a decompression illness (known as cutis marmorata). These alterations are usually transient, but they could be a warning sign of a more severe manifestation of decompression illness.
Keywords: Cutis marmorata; decompression illness; scuba diving